Beyond UTAUT: Integrating Digital Literacy and Voluntariness of Use to Understand Cashless Payment Behavior - Asri, Damayanti Kurnia; Tamtomo, Jani; Billah, Muhammad Kafa; Simanjuntak, Evi Rinawati (Jurnal Aplikasi Manajemen, 2025)
Adopting digital payment systems is crucial for developing MSMEs, particularly in emerging regions with limited digital infrastructure. This study addresses the knowledge gap regarding digital payment adoption in areas that are not entirely digitally connected, such as Ibu Kota Nusantara (IKN), the new capital of Indonesia. The study aims to identify the factors influencing MSME owners' behavioral intention and usage behavior regarding digital payment systems, using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. This study employs a survey method with a convenience sampling technique, involving 350 MSME owners in IKN and its surrounding areas. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that performance expectancy, social influence, and facilitating conditions significantly influence behavioral intention to adopt digital payments. However, effort expectancy does not significantly affect the intention to use digital payments. Additionally, facilitating conditions and behavioral intention impact usage behavior significantly. No evidence supported the moderating role of voluntariness of use in the relationship between social influence and behavioral intention. Digital literacy was found to moderate the relationship between behavioral intention and usage behavior, highlighting the critical role of digital literacy in technology adoption. This study provides important contributions to understanding the factors influencing digital payment adoption in developing regions.